(untitled) (Journal of the College of Basic Education, 2022)
The study included confirming the diagnosis of 29 isolates of Pseudomonas aeruginosa bacteria based on culture, microscopic and biochemical tests, and two isolates of Saccharomyces cerevisiae, as well as collecting 12 diseased isolates from multiple clinical samples from some hospitals in the city of medicine, including Staphylococcus aureus, Escherichia coli. The diagnosis of all isolates was confirmed by the VITEK2 system and according to the card for gram-negative and gram-positive bacteria in addition to the card for yeast, then a sifting was conducted for Pseudomonas aeruginosa isolated from wounds, burns and sputum for the purpose of choosing the most efficient isolate in the production of pyocyanin dye. It has the highest concentration and recorded the highest absorption, which is the best in the production of pyocyanin dye.The sensitivity of pathogenic bacteria to 10 types of antibiotics was tested, and the results showed that most of the isolates were resistant to (Ciprofloxacin, Imipenem, Amikacin) and the effect was different for the rest of the antibiotics. Yeast Super maya of Chinese origin and isolate By2 of Glorpan yeast of Chinese origin. A sifting of isolates of S.cerevisiae was also carried out in order to select the isolate most efficient in the production of inhibitory proteins using the method of diffusion in the pits to know the effect of these substances against the pathogenic bacteria under study.The results showed that isolate By 1 gave the highest inhibition rate towards S.aureus and E.coli isolates than isolate By 2. Also, the minimum inhibitory concentration (MIC) of Pyocyanin and S.cerevisiae was measured against the bacterial isolates under study. Using the method of turbidity in tubes, and the results proved that the value of ̒ MIC varied according to the concentration of the filtrate and its effectiveness and according to the gradation of pathogenic bacteria. The synergistic relationship between Pyocyanin dye and S.cerevisiae filtrate towards pathogenic bacteria selected for this test according to the degree of their resistance to antibiotics was also studied.The results showed that the relationship was synergistic and there was no other relationship due to the effectiveness of the dye with the filter on inhibiting the action of pathogenic bacteria. Therefore, the study recommends focusing on the Pyocyanin dye with Saccharomyces cerevisiae (as a whole cell or the inhibitory substances it produces) as a treatment for infections caused by some types of pathogenic bacteria.